Monetary and Fiscal Policies Interactions on Stock Returns in Nigeria - Onanuga Idowu; Ilo Bamidele; Lucas Elumah (Binus Business Review, 2020)
This research examined the effects of monetary and fiscal policies on stock returns in Nigeria. The researchers utilized ex-post facto research design using the time series data of the annual market values of All Share Index (ASI) of the Nigerian Stock Exchange (NSE). It was yearly data on the various monetary policy and fiscal policy variables obtained from the Central Bank of Nigeria Statistical Bulletins covering from 1985 to 2017. The result of the cointegration test reveals a long-run relationship between monetary variables and stock returns. Meanwhile, the overall result shows that monetary policy has a significant effect on stock return. However, there is no long-run relationship between fiscal policy variables and stock returns. Meanwhile, the result of the Unrestricted Vector Autoregression model shows that fiscal policy has a significant effect on stock prices in Nigeria. On the other hand, a long-run relationship exists between monetary policy, fiscal policy, and stock returns. It has a significant effect on stock returns in Nigeria. This implies that monetary and fiscal policies have a significant effect on stock returns in Nigeria. It is recommended that there is a need for the federal government to harmonize fiscal and monetary policies in the same direction and to equally design policies that promote a free market for the growth of the Nigerian economy.